Single‐Atom Co‐Decorated MoS2 Nanosheets Assembled on Metal Nitride Nanorod Arrays as an Efficient Bifunctional Electrocatalyst for pH‐Universal Water Splitting. (20th April 2021) - Doan, Thi Luu Luyen; Nguyen, Dinh Chuong; Prabhakaran, Sampath; Kim, Do Hwan; Tran, Duy Thanh; Kim, Nam Hoon; Lee, Joong Hee
Abstract: The commercialization of electrochemical water splitting technology requires electrocatalysts that are cost‐effective, highly efficient, and stable. Herein, an advanced bifunctional electrocatalyst based on single‐atom Co‐decorated MoS2 nanosheets grown on 3D titanium nitride (TiN) nanorod arrays (CoSAs‐MoS2 /TiN NRs) has been developed for overall water splitting in pH‐universal electrolytes. When applied as a self‐standing cathodic electrode, the CoSAs‐MoS2 /TiN NRs requires overpotentials of 187.5, 131.9, and 203.4 mV to reach a HER current density of 10 mA cm –2 in acidic, alkaline, and neutral conditions, respectively, which are superior to the most previously reported non‐noble metal HER electrocatalysts at the same current density. The CoSAs‐MoS2 /TiN NRs anodic electrode also shows low OER overpotentials of 454.9, 340.6, and 508.0 mV, respectively, at a current density of 10 mA cm –2 in acidic, alkaline, and neutral mediums, markedly outperforming current OER catalysts reported elsewhere. More importantly, an electrolyzer delivered from the cathodic and anodic CoSAs‐MoS2 /TiN NRs electrodes exhibits an extraordinary overall water splitting performance with good stability and durability in pH‐universal conditions. Abstract : Hierarchical heterostructures containing single‐atom Co‐decorated MoS2 nanosheets assembled on TiN nanorod arrays are developed as bifunctional 3D electrocatalysts for HER and OER under a wide pH range electrolyte. In practical application, the CoSAs‐MoS2 /TiN NRs‐based electrolyzer demonstrates high performance and stability for pH‐universal overall water splitting.